2022
DOI: 10.1186/s12874-022-01577-x
|View full text |Cite
|
Sign up to set email alerts
|

Methodological conduct of prognostic prediction models developed using machine learning in oncology: a systematic review

Abstract: Background Describe and evaluate the methodological conduct of prognostic prediction models developed using machine learning methods in oncology. Methods We conducted a systematic review in MEDLINE and Embase between 01/01/2019 and 05/09/2019, for studies developing a prognostic prediction model using machine learning methods in oncology. We used the Transparent Reporting of a multivariable prediction model for Individual Prognosis Or Diagnosis (TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 135 publications
1
54
0
Order By: Relevance
“…While recent studies have revealed the advantage of immune-related gene pairs in developing prognostic signatures 36, 52 , the quadratic number of candidate genes still complicates the modeling process. Recent efforts focused on the improvement of machine-learning algorithms for variable selection and model fittings, which remain of poor quality in oncology 77 . Unlike those studies, TimiGP is an efficient algorithm to identify gene pairs representing functional inter-cell interactions, namely, a computational-friendly feature selector based on biological and clinical insights.…”
Section: Discussionmentioning
confidence: 99%
“…While recent studies have revealed the advantage of immune-related gene pairs in developing prognostic signatures 36, 52 , the quadratic number of candidate genes still complicates the modeling process. Recent efforts focused on the improvement of machine-learning algorithms for variable selection and model fittings, which remain of poor quality in oncology 77 . Unlike those studies, TimiGP is an efficient algorithm to identify gene pairs representing functional inter-cell interactions, namely, a computational-friendly feature selector based on biological and clinical insights.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome most of these challenges in the correlation of oil viscosity, soft-computing and machine learning-based computational models were adopted in estimating the viscosity of crude oil. Linear regression, artificial neural networks, support vector machines, decision tree and so many other machine learning methods (see [35][36][37][38][39][40][41][42][43][44]) have been reported to have performed more efficiently than conventional empirical correlations. A study that involved predicting the viscosity of crude oil samples from Nigeria using a neural network with 0.99 as the coefficient of correlation presented an improved performance when compared to already developed empirical correlations.…”
Section: Introductionmentioning
confidence: 99%
“…However, these ML models still see limited use in the clinical practice [18]. Their poor adoption may be attributed to the black-box nature that complicates model interpretability, a high risk of bias, and the need for larger training datasets to achieve similar performance, as compared to linear Cox regression [19].…”
Section: Introductionmentioning
confidence: 99%